The bones of the Milky Way - Goodman, Alyssa A.; Smith, Rowan J. (The astrophysical journal, 2014)
The very long and thin infrared dark cloud “Nessie” is even longer than had been previously claimed, and an analysis of its Galactic location suggests that it lies directly in the Milky Way's mid-plane, tracing out a highly elongated bone-like feature within the prominent Scutum-Centaurus spiral arm. Re-analysis of mid-infrared imagery from the Spitzer Space Telescope shows that this infrared dark cloud (IRDC) is at least two and possibly as many as five times longer than had originally been claimed by Nessie's discoverers; its aspect ratio is therefore at least 300:1 and possibly as large as 800:1. A careful accounting for both the Sun's offset from the Galactic plane (∼25 pc) and the Galactic center's offset from the (lII , bII ) = (0, 0) position shows that the latitude of the true Galactic mid-plane at the 3.1 kpc distance to the Scutum-Centaurus Arm is not b = 0, but instead closer to b = -0.4, which is the latitude of Nessie to within a few parsecs. An analysis of the radial velocities of low-density (CO) and high-density (NH3) gas associated with the Nessie dust feature suggests that Nessie runs along the Scutum-Centaurus Arm in position-position-velocity space, which means it likely forms a dense “spine” of the arm in real space as well. The Scutum-Centaurus Arm is the closest major spiral arm to the Sun toward the inner Galaxy, and, at the longitude of Nessie, it is almost perpendicular to our line of sight, making Nessie the easiest feature to see as a shadow elongated along the Galactic plane from our location. Future high-resolution dust mapping and molecular line observations of the harder-to-find Galactic “bones” should allow us to exploit the Sun's position above the plane to gain a (very foreshortened) view “from above” the Milky Way's structure.
Gesehen am 20.10.2020